SOCIAL CONFLICT: THE BASIS OF SOCIAL DEVELOPMENT - Mamatkulov Rashid Pazilbekovich (American Journals Publishing, 2023)
The article philosophically and socially analyzes the concept of conflict. Based on the principle of justice, the new values entering social relations in the conditions of the market economy are explained through the methods of analysis, synthesis, comparison, deduction, and induction. The dialectics, harmony, and mutual necessity of the categories of relative resistance and conflict are described. Relevant conclusions and recommendations are given.
Keywords: society, social, development, approach, value.